Feminism och regeringen Löfven: En idéanalys av Sveriges feministiska utrikespolitik - Andersson,Lydia (2018)
Since 2014 the Swedish government has had a feminist foreign policy. This thesis aims to examine which kind of feminism the policy is built upon. To investigate this a content analysis with a focus on ideas was used. Three different ideal types of feminism were set up from liberal, radical and socialist feminism. The material examined was made up of different official documents from the government through the ministry of foreign affairs and the foreign affairs administration and also speeches and articles from the minister of foreign affairs Margot Wallström. The result show that the feminist foreign policy builds upon ideas of liberal feminism. Some tendencies towards radical- and socialist feminism were also present but their key issues were not addressed and liberal feminism was the most recurrent. This can to some extent be explained by the fact that liberal feminism is the most mainstream and modest of the three. As foreign policy is a very sensitive area it is therefore not surprising that liberal feminism is the kind of feminism that the policy builds upon.
Keywords: feminism; utrikespolitik; idealtyper; liberalfeminism; radikalfeminism; socialistisk feminism